Pro-Environmental Behaviour of Big City Employees in Rasch Model and SEM Outlook: A Preliminary Finding - Herlina Maria Grace; Lusia Erma; Rivaldo (E3S Web of Conferences, 2023)
Human activity significantly contributes to many of the world's current environmental concerns. Pro-environmental behaviors (PEBs) at the workplace can help organizations improve their environmental performance. Therefore, the goal of this study is to provide an explanation for employees' ecologically beneficial conduct in large cities. The three hypotheses of this study were proven significantly. Rasch Model Analysis and structural equation modeling (SEM) with second-order confirmatory factor analysis confirmed all the hypotheses. Eco initiatives significantly influence pro-environmental behavior, and eco-helping influences pro-environmental behavior significantly. The final one, eco-civic involvement, significantly impacts pro-environmental behavior. According to the findings of two statistical approaches used to analyze data, the environmentally friendly behaviors of employees in big cities are still limited to the behavior of good employees within the firm. It implies that pro-environmental behavior among city workers has not yet been motivated by personal initiative. On the other hand, the Rasch Model and SEM analysis results suggest that employees in big cities are environmentally sensitive as part of their organization's good citizenship.